Body Builder Chatbot - Chok, Martin Siang Zhen (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This project aims to develop a chatbot for bodybuilding enthusiasts. There are bodybuilders that do not have access to bodybuilding information, face budget constraints and without proper guidance. All of these reasons will lead them to use incorrect methods during their bodybuilding process. With the development of this chatbot, these problem can be overcome. The chatbot will be able to provide information on exercises, training routines, and nutrition plans. The chatbot will be trained on a dataset of bodybuilding information and will utilize natural language processing techniques to understand and respond to user queries. The goal of this project is to provide an accessible and convenient tool for individuals to improve their bodybuilding knowledge and progress. The implementation and testing of the chatbot demonstrates its effectiveness in accurately understanding user queries and providing relevant and reliable information. With future works including expanded features, multilingual support, and integration with wearable devices, the chatbot holds great potential to further assist users in their bodybuilding journeys and contribute to their overall fitness goals.